SUMO1 Promotes Mesangial Cell Proliferation Through Inhibiting Autophagy in a Cell Model of IgA Nephropathy - Tan, Xia; Liu, Yexin; Liu, Di; Tang, Xiaofang; Xia, Ming; Chen, Guochun; He, Liyu; Zhu, Xuejing; Liu, Hong (Frontiers in Medicine, 2022)
IgA nephropathy(IgAN) is a common form of primary glomerulonephritis and its main pathological changes are mesangial cell proliferation and matrix expansion. Autophagy inhibition may result in its mesangial cell proliferation and renal lesions. SUMOylation is a eukaryotic-reversible post-translational modification where SUMO are covalently attached to target proteins to regulate their properties. It is largely unclear if SUMOylation contributes to the pathogenesis of IgAN. This study was designed to investigate the change of protein SUMO1 in mesangial cells of IgAN and its association with autophagy. We found the expression of SUMO1 was up-regulated in IgAN, IgA mouse model and aIgA1 stimulated mesangial cells. In aIgA1 stimulated mesangial cell model, we tested LC3Ⅱ/Ⅰ and p62, the autophagy-related proteins suggested the inhibition of autophagy. Inhibited SUMOylation with Ginkgolic Acid(GA) or silencing SUMO1 could down-regulate SUMO1 and SUMO1-p53, promote autophagy and lessen cell proliferation. In summary, in the mesangial cells stimulated with aIgA1, SUMO1 may contribute to its cell proliferation through inhibited autophagy and SUMO1-p53 may play a role in this process.